2010
DOI: 10.1038/oby.2009.185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity Among Children With Chronic Conditions

Abstract: New evidence suggests that children with chronic conditions may be predisposed to overweight and obesity. This study provides prevalence estimate of obesity for children and adolescents with select chronic conditions. We analyzed reported height and weight and the corresponding BMI from 46,707 subjects aged 10–17 years collected by the National Survey of Children's Health (NSCH‐2003). Our main outcome measure was the prevalence of obesity (defined as ≥95th percentile of the sex‐specific BMI for age growth char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
138
1
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(165 citation statements)
references
References 21 publications
17
138
1
9
Order By: Relevance
“…Following this trend in obesity, studies have found an increased prevalence of asthma in children who are obese, which suggests the possibility that asthma and obesity may be causally related in some way (Castro-Rodriguez, Holberg, Morgan, Wright, & Martinez, 2001;Chen, Kim, Houtrow, & Newacheck, 2009). Furthermore, there is evidence to suggest that there is a negative relationship between obesity and asthma (Belamarich et al, 2000;Musaad et al, 2009).…”
Section: Introduction Statement Of the Problemmentioning
confidence: 99%
“…Following this trend in obesity, studies have found an increased prevalence of asthma in children who are obese, which suggests the possibility that asthma and obesity may be causally related in some way (Castro-Rodriguez, Holberg, Morgan, Wright, & Martinez, 2001;Chen, Kim, Houtrow, & Newacheck, 2009). Furthermore, there is evidence to suggest that there is a negative relationship between obesity and asthma (Belamarich et al, 2000;Musaad et al, 2009).…”
Section: Introduction Statement Of the Problemmentioning
confidence: 99%
“…For example, in a study of children with a wide array of chronic conditions using data from the National Survey of Children ' s Health (Chen et al, 2010), youths aged 10 to17 with certain conditions were at increased risk for obesity compared to children without chronic illnesses. Specifi cally, the prevalence of obesity was 19.7% among children with asthma, 18.4% among children with a hearing/vision condition, 19.3% among those with a learning disability, 23.4% for youths with autism, and 18.9% among children with ADHD, as compared to 12.2% among those without a condition.…”
Section: Chronic Health Conditions and Obesitymentioning
confidence: 99%
“…7,8 The core symptoms of ADHD, which include inattention, hyperactivity and impulsivity, are associated with significant impairment across children's academic, social and familial functioning. 9 In terms of health-related outcomes, elevated rates of obesity have been observed in adults, 10 adolescents 11 and young children with ADHD in both epidemiological and clinical samples 6,12,13 that persist after controlling for gender, diet and activity patterns, socioeconomic status (SES) and psychiatric comorbidities. Similar associations with obesity have been found when inattention and impulsivity are measured dimensionally using neuropsychological tests.…”
Section: Introductionmentioning
confidence: 99%